Family Dinner at Frances Kamp Celebrating Cliff and Evie Macabee's 40th Anniversary - Watkins, Howard::::::::: (1988)
Adam Watkins, Robin Watkins and Evie Macabee seated Fran's home at 6300 N. Palm Avenue #109, Fresno